Evaluation of standardized triple intrathecal therapy toxicity in oncohematological adult patients - Valentín Cabañas-Perianes; María Sacramento Díaz-Carrasco; Raquel Olmos-Jiménez; Manuel Valderrey-Pulido; Alberto Espuny-Miró (Farmacia Hospitalaria)
Objective: To assess the toxicity of a standardized triple intrathecal chemotherapy in onco- hematological adult patients and to establish risk factors of toxicity. Method: Observational and prospective study of standardized triple intrathecal chemotherapy administrations in onco-hematologic adult patients for 18 months. Results: There were some adverse events in 39.3% of the 56 administrations registered. 96.7% of the events were grade 1-2 and only 1 event was grade 3. The lower age of the patient and the greater difference between the administered drug volume and cerebrospinal fluid removed volume were shown as risk factors for toxicity. Conclusions: The administration of standardized triple intrathecal chemotherapy was related to a low frequency of toxicity and most of adverse events were mild-moderate. The detection of adverse effects was significantly greater in young adults and in those administrations where the difference between cerebrospinal fluid remove volume and the administered drug was greater